2002
DOI: 10.1359/jbmr.2002.17.7.1230
|View full text |Cite
|
Sign up to set email alerts
|

Onion and a Mixture of Vegetables, Salads, and Herbs Affect Bone Resorption in the Rat by a Mechanism Independent of Their Base Excess

Abstract: Prevention of low bone mass is important to reduce the incidence of osteoporotic fractures. In man, the consumption of fruits and vegetables is associated with greater bone mineral density (BMD), an effect that is claimed to be caused by their base excess buffering metabolic acid, thought to dissolve bone. We showed previously that in the rat the consumption of several vegetables, salads, and herbs inhibits bone resorption and that onion increases bone mass. In this study we show that, although the intake of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 29 publications
2
67
2
2
Order By: Relevance
“…A recent 2-year randomized, controlled trial found that supplementation with potassium citrate or three additional portions of fruit and vegetables a day did not reduce bone turnover or increase BMD, suggesting that any long-term benefits of fruit and vegetable intake on bone are not due to the provision of alkaline salts. (8) Animal studies have shown that ovariectomy-induced bone resorption can be inhibited by onions and other vegetables commonly eaten by humans (9) and that this effect is independent of their base-balancing properties, (10) indicating that the protective effects of fruit and vegetables may be found in the nutrients they contain.…”
Section: Introductionmentioning
confidence: 99%
“…A recent 2-year randomized, controlled trial found that supplementation with potassium citrate or three additional portions of fruit and vegetables a day did not reduce bone turnover or increase BMD, suggesting that any long-term benefits of fruit and vegetable intake on bone are not due to the provision of alkaline salts. (8) Animal studies have shown that ovariectomy-induced bone resorption can be inhibited by onions and other vegetables commonly eaten by humans (9) and that this effect is independent of their base-balancing properties, (10) indicating that the protective effects of fruit and vegetables may be found in the nutrients they contain.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary 3 H-TC increased when the diets of 2 month-old male rats were changed from 1.1 g Ca/100 g dry weight to 0.2 g Ca/100 g dry weight in an acute setting [13]. Others [14,15] have also demonstrated changes in urinary 3 H-TC levels in an acute setting during dietary interventions that lasted for ~10 days. There is a paucity of data that examines urinary 3 H-TC in a chronic setting.…”
Section: Resultsmentioning
confidence: 98%
“…For example, it has been reported that onion, garlic and parsley can inhibit bone resorption in ovariectomized rats (22,23). Quercetin from onion extract inhibits the differentiation of osteoclast progenitor into pre-osteoclasts and actin ring formation (24).…”
Section: Discussionmentioning
confidence: 99%